Lessons from the damned: queers, whores, and junkies respond to AIDS - Stoller, Nancy E. (Routledge, 1998)
"Lessons from the Damned challenges the notion that public health theories and official organizations have the greatest impact on the fight against AIDS. Instead, Stoller looks closely at the ways the most disenfranchised - the poor, people of color, drug users, gay men and lesbians, and women - have built social movements to fight the epidemic. Drawing upon extensive ethnographic research and the words of the activists themselves, as well as the literature of social movements and theories of bureaucracy, Stoller offers guidelines for dealing with diversity and conflict and also with both theoretical and practical perspectives on cross-community and international organizing."–BOOK JACKET.
Section: xvi, 175 pages : illustrations ; 24 cm
Keywords: 1900-1999; 1980-1989; 1990-1999; amériques; approches et analyses; capitalisme; care; cours; discipline; histoire et politique; hétérosexisme; justice sociale; militance; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; sida; soc2014; sociologie; sofia; systèmes d'oppressions; thématiques; états-unis

The death of nature: Women, ecology and the scientific revolution - Merchant, Carolyn (New York : Harper & Row, 1983)
Un examen de la révolution scientifique qui montre comment la vision mécaniste du monde de la science moderne a sanctionné l'exploitation de la nature, l'expansion commerciale sans retenue et un nouvel ordre socio-économique qui subordonne les femmes.
Keywords: approches et analyses; capitalisme; discipline; environnement; histoire; histoire des sciences; histoire et politique; incontournable; patriarcat; philosophie; progrès; projet charge mentale; santé; sciences humaines; systèmes d'oppressions; thématiques; violences; violences envers la nature; violences envers les femmes*; écoféminisme